2022
DOI: 10.1002/cctc.202200886
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Semi‐Hydrogenations of Alkynes by First‐Row (3d) Transition Metal Catalysts

Abstract: Dedicated to Matthias Beller on the occasion of his 60 th birthdayChemCatChem www.chemcatchem.org

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 251 publications
(291 reference statements)
0
11
0
Order By: Relevance
“…Achieving stereo‐chemical control in this reaction is a long‐standing challenge and continues to be the subject of intensive investigation [84] . Nevertheless, appreciable progress has been made in this direction by applying 3d base metal‐based catalysts [85] …”
Section: Hydrogenation Reactions Using Cr Mo and Wmentioning
confidence: 99%
“…Achieving stereo‐chemical control in this reaction is a long‐standing challenge and continues to be the subject of intensive investigation [84] . Nevertheless, appreciable progress has been made in this direction by applying 3d base metal‐based catalysts [85] …”
Section: Hydrogenation Reactions Using Cr Mo and Wmentioning
confidence: 99%
“…For instance, it was recently discovered that Mn−PR 2 moieties are reactive toward H 2 and, [29] intriguingly, that cis ‐vinyl inserted Mn(I) intermediate complexes react with H 2 to form a trans ‐alkene product, exclusively, without cis to trans isomerization [30] . This selectivity mode is in contrast to the normal cis to trans isomerization mode in mononuclear catalysts [12,31] . It was further demonstrated that the catalytic platform can be assembled in situ directly from Mn 2 (CO) 10 and phosphine (R 2 PH) without the need for isolation.…”
Section: Introductionmentioning
confidence: 97%
“…The catalytic relevance of this cooperative mechanism is demonstrated in the selective semihydrogenation of diphenylacetylene to Z- stilbene under mild conditions, with a comparable performance to recently disclosed Ni-based systems. 5,[43][44][45][46][47]…”
Section: Introductionmentioning
confidence: 99%